KAJIAN FILOLOGIS TERHADAP IDENTITAS DAN EDISI TEKS STANDAR NASKAH PODA NI HATA-HATA NI PAGAR PAMUHUNAN (NO. INV. 3052/07.237) KOLEKSI MUSEUM NEGERI PROVINSI SUMATERA UTARA - Mery Grace Jenita Saragi; Herlina Herlina; Warisman Sinaga (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to examine the identity and produce a standard text edition of the manuscript Poda ni Hata-Hata ni Pagar Pamunuhan (Inventory No. 3052/07.237), which is part of the collection of the North Sumatra Provincial State Museum. The research employs a philological approach to uncover the manuscript’s physical characteristics, cultural background, and content. The methodology includes inventorying, physical description, transliteration, and the preparation of a standard edition based on textual criticism principles. The findings reveal that the manuscript is written on bark material using Batak script and contains traditional teachings and moral advice passed down through generations in Batak society. The text editing process resulted in a valid standard edition, complete with critical apparatus and restored readings. This study highlights the importance of preserving traditional manuscripts as intangible cultural heritage rich in historical, linguistic, and educational values. The resulting edition is expected to serve as a foundational reference for further studies in philology, regional literature, and Batak cultural heritage.